The Impact of Digital Communication on the Grammar and Lexicon of the Russian Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The rapid development of digital communication has significantly altered linguistic norms across global languages, including Russian. In contemporary Russian, the proliferation of social networks, messengers, and blogging platforms has led to widespread integration of English loanwords, stylistic informality, and syntactic simplifications. While prior studies have noted these trends, comprehensive analyses combining corpus linguistics, grammar, and lexical change within digital Russian communication remain underexplored. This study investigates the impact of digital interaction on the grammatical and lexical dimensions of the Russian language, focusing on how digital discourse influences structural norms and introduces new communicative practices. Through corpus analysis of over 10,000 messages, the study identifies the dominance of anglicisms, frequent abbreviation use, grammatical simplification, and emoji-based emotional substitution in youth-oriented digital exchanges. These shifts not only alter word formation and syntax but also reshape written Russian into a hybrid expressive medium. The research provides a data-driven evaluation of linguistic transformation in real-time digital environments, highlighting the creative adaptation of foreign elements and informal grammar as emerging features of Russian digital discourse. These findings necessitate educational and linguistic policy interventions to balance innovation with preservation of literary standards, while suggesting further research on long-term impacts of digital language evolution on formal education, cultural identity, and intergenerational communication.